Mass Communication Paradigm in the Construction of Fatwa on Terrorism - Kawai, Bunga Bidadari Alexandra Natsumi; Sari, Karmila Ratna; Noviana, Fina; Munadhifah, Indah; Pamaungkas, Septi Yuliana; Ma’alia, Ayu; Kharisah, Kharisah; Faisal, Muhammad (International Tatho Academics, 2025)
The purpose of this qualitative research with a philosophical normative approach is to identify the paradigm of mass communication function in the construction of the 2004 fatwa of the Indonesian Ulema Council on Terrorism. The research data was obtained through documentation techniques. Meanwhile, the analysis approach uses content analysis, and the data is analyzed through reduction, presentation and verification. This study concludes that there is a paradigm of mass communication functions in the construction of the fatwa on terrorism, including the function of social supervision in formal forms such as government regulations and informal laws such as social norms and values held by the community. Then, the function of social transmission in the positive aspects of attitudes, values, beliefs, and habits taught to the public on the importance of human values, and internalized through strict laws against perpetrators of terrorism. This research confirms that preventive efforts against terrorism can be internalized through religious literacy as a social communication tool.